2011
DOI: 10.1007/s00027-011-0193-8
|View full text |Cite
|
Sign up to set email alerts
|

Flow intermittence controls leaf litter breakdown in a French temporary alluvial river: the “drying memory”

Abstract: The inputs and breakdown of terrestrial leaf litter in streams is a fundamental ecological process that sustains in-stream foodwebs and secondary production. In temporary rivers, litter breakdown is reduced during dry phases, but the long-term effect of alternating drying and wetting cycles on litter breakdown is still poorly understood. We tested the hypothesis that leaf litter breakdown (LLB) in temporary rivers is primarily controlled by flow permanence (the number of flowing days over a given period expres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
114
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 107 publications
(126 citation statements)
references
References 42 publications
10
114
2
Order By: Relevance
“…The fact that leaf litter breakdown was detectable under permanently dry conditions could be explained by alternative mechanisms such as leaching and photodegradation (Dieter et al 2011). Datry et al (2011) found that that dry phase duration influenced litter decomposition rates primarily because of the negative effects of the dry phase on invertebrate shredders, and that this effect extended long after rewetting, as if there was a dry event ''memory''. They observed that drying events affected the performance of the decomposing biota and thus the decomposition rates of leaf litter.…”
Section: Scope Of the Special Issuementioning
confidence: 99%
“…The fact that leaf litter breakdown was detectable under permanently dry conditions could be explained by alternative mechanisms such as leaching and photodegradation (Dieter et al 2011). Datry et al (2011) found that that dry phase duration influenced litter decomposition rates primarily because of the negative effects of the dry phase on invertebrate shredders, and that this effect extended long after rewetting, as if there was a dry event ''memory''. They observed that drying events affected the performance of the decomposing biota and thus the decomposition rates of leaf litter.…”
Section: Scope Of the Special Issuementioning
confidence: 99%
“…This knowledge gap limits our understanding of the range of pathways that exist for allochthonous organic matter processing in rivers. There is evidence suggesting that emersion inhibits colonization of leaf litter by aquatic leafshredding invertebrates, and that immersion duration and frequency influence litter breakdown in temporary river habitats (Boulton 1991;Langhans and Tockner 2006;Datry et al 2011). The effects of emersion on micro-organisms colonizing leaf litter and on microbial decomposition are less clear.…”
Section: Introductionmentioning
confidence: 98%
“…The repeated onset and cessation of flow causes temporary rivers to contract and expand in the lateral and longitudinal dimensions, alternately immersing and exposing channel sediments. Temporary rivers are very common, but the state of knowledge concerning organic matter dynamic in these rivers is poor (Larned et al 2010a;Datry et al 2011). This knowledge gap limits our understanding of the range of pathways that exist for allochthonous organic matter processing in rivers.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Flow is highly variable within these streams, and has been shown to affect organic matter breakdown (Fischer et al 2002, Claret and Boulton 2003, Datry et al 2011. Organic matter in this study was based on observed differences in levels of detritus (as leaf litter) and coal, however types of organic matter and carbon have not been quantified.…”
Section: Sediment Carbon and Nitrogenmentioning
confidence: 99%